IMPROVING THE PERFORMANCE OF MSMEs THROUGH INNOVATION, FINANCIAL LITERACY, AND DIGITALIZATION - Desmiyawati Desmiyawati; Susilatri Susilatri; Sinta Ramaiyanti; Nur Azlina (JRAK, 2023)
The Covid pandemic has had a significant impact on MSMEs in Indonesia. Surveys conducted during this period showed a decline in the performance of MSMEs, although some studies showed inconsistent results. The study aims at examining the impact of innovation, financial literacy, and digitalization on the performance of MSMEs in the Riau Region. The samples used in this study were MSMEs located in Riau Province. Data obtained through the distribution of questionnaires and interviews were analyzed using multiple linear regression. Then, test findings showed that digitalisation and innovation had a significant impact on performance. Meanwhile, financial literacy did not affect the performance of MSMEs. The implications of this research for MSMEs were the use of technology and innovation, especially product marketing that can reach a broader market so that it can improve MSME performance. As for researchers, it can be a reference for the development of subsequent research.